A COMPUTATIONAL STUDY ON Ca²⁺ MODULATION OF ASIC 1 PHARMACOLOGIC PROPERTIES - NICULAE, Raluca; MERNEA, Maria; GHICA, Loredana; MIHĂILESCU, Dan Florin (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Acid-sensing ion channel (ASIC) is involved in important processes like synaptic plasticity and learning, fear and anxiety, pain sensation. Due to its role in neurodegeneration and neuroinflammation, the channel is a viable pharmacological target. The channel is activated by acid pH pulses and it rapidly desensitizes; therefore the channel can exist in open, closed and desensitized states. Here we performed a molecular docking study of some ASIC1 ligands like amiloride, cocaine, histamine, ibuprofen, sinomenine and Zn2+ in the transmembrane region of ASIC1 channel models in different states (closed, open and desensitized). Also, since channel properties are influenced by Ca2+, we performed a set of calculations when Ca2+ is present in the channel pore. In addition, we modelled mutant channels in different states with substitutions of residues forming Ca2+ binding sites. The interaction of ligands with mutant channel models was investigated in the presence and absence of Ca2+. Our results show an affinity of ASIC1 for ibuprofen, followed by Zn2+, histamine and amiloride. Sinomenine and cocaine do not appear as ASIC1 ligands regardless of channel state. Overall, Ca2+ enhances the interactions of ligands with the channels, including the interactions of cocaine that is not recognized as an ASIC1 ligand. The effect of mutations is to reduce the favourable interactions with ligands. The results obtained on the three channel states are consistent, showing that results are not significantly influenced by the choice of model. Our results bring new information on ASIC1 pharmacological modulation by showing that Ca2+ presence in the pore enhances channel affinity for ligands.